Proses, Tantangan, dan Faktor Keberhasilan Transformasi Agile: Kajian Literatur Sistematis - ramadhany, emha diambang; wirapraja, Alexander; Afandi, Khoirunnisa; Arief, M. Habibullah (LPPM Universitas dr. Soebandi, 2023)
The waterfall software development method has been considered as a traditional method towards modern software development using Agile methods which are considered sufficient in current conditions which emphasize the speed of data and information exchange and indirectly emphasize the life cycle and fast social interaction between individuals who involved in the organization in the development of information technology, in researching the development of the agile method related to key factors, challenges and the transition process from the old system to the new system, data collection and related theories were carried out, using a literature study approach by collecting agile method data. The results obtained were mentioned the factors driving the application of agile methods along with the success factors and failure factors in implementing Agile methods.